Ordinary differential equations - Greenberg, Michael D. (Wiley, 2012)
"After a brief review of first-order differential equations, this book focuses on second-order equations with constant coefficients that derive their general solution using only results described previously. Higher-order equations are provided since the patterns are more readily grasped by students. Stability and fourth order equations are also discussed since these topics typically appear in further study for engineering and science majors. In addition to applications to engineering systems, applications from the biological and life sciences are emphasized. Ecology and population dynamics are featured since they involve both linear and nonlinear equations, and these topics form one application thread that weaves through the chapters. Diffusion of material, heat, and mechanical and electrical oscillators are also important in biological and engineering systems and are discussed throughout. A complete Instructor Solution Manual is available upon request and contains solutions to all exercises as well as Maple[trademark symbol] code. While the book is not dependent on the use of one specific software, some of the exercises do call on the use of such systems to solve certain differential equations or to plot the results. A Student Solutions Manual is available to supplement the book, and while the first manual will feature Maple, the author is also preparing versions using Mathematica and MATLAB;to accommodate instructor preferences. Chapter coverage includes First-Order Differential Equations; Higher-Order Linear Equations; Applications of Higher-Order Linear Equations; Systems of Linear Differential Equations; Laplace Transform; Series Solution; Systems of Nonlinear Differential Equations; and Appendices on Partial Fraction Expansions, Determinants, Gauss Elimination, and Complex Numbers and the Complex Plane"--Provided by publisher.